A doxycycline inducible, adenoviral bone morphogenetic protein‐2 gene delivery system to bone. (12th June 2017) - Bara, Jennifer J.; Dresing, Iska; Zeiter, Stephan; Anton, Martina; Daculsi, Guy; Eglin, David; Nehrbass, Dirk; Stadelmann, Vincent A.; Betts, Duncan C.; Müller, Ralph; Alini, Mauro; Stoddart, Martin J.
Abstract: We report the novel use of a tuneable, non‐integrating viral gene delivery system to bone that can be combined with clinically approved biomaterials in an 'off‐the‐shelf' manner. Specifically, a doxycycline inducible Tet‐on adenoviral vector (AdTetBMP‐2) in combination with mesenchymal stromal cells (MSCs), fibrin and a biphasic calcium phosphate ceramic (MBCP®) was used to repair large bone defects in nude rats. Bone morphogenetic protein‐2 (BMP‐2) transgene expression could be effectively tuned by modification of the doxycycline concentration. The effect of adenoviral BMP‐2 gene delivery upon bone healing was investigated in vivo in 4 mm critically sized, internally fixated, femoral defects. MSCs were transduced either by direct application of AdTetBMP‐2 or by pre‐coating MBCP granules with the virus. Radiological assessment scores post‐mortem were significantly improved upon delivery of AdTetBMP‐2. In AdTetBMP‐2 groups, histological analysis revealed significantly more newly formed bone at the defect site compared with controls. Newly formed bone was vascularized and fully integrated with nascent tissue and implanted biomaterial. Improvement in healing outcome was achieved using both methods of vector delivery (direct application vs. pre‐coating MCBP). Adenoviral delivery of BMP‐2 enhanced bone regeneration achieved by the transplantation of MSCs, fibrin and MBCP in vivo . Importantly, our in vitro and in vivo data suggest that this can be achieved with relatively low (ng/ml) levels of the growth factor. Our model and novel gene delivery system may provide a powerful standardized tool for the optimization of growth factor delivery and release for the healing of large bone defects. Copyright © 2016 John Wiley & Sons, Ltd.